2022
DOI: 10.21037/tau-22-220
|View full text |Cite
|
Sign up to set email alerts
|

Patchouli alcohol suppresses castration-resistant prostate cancer progression by inhibiting NF-κB signal pathways

Abstract: Background: There is evidence that patchouli alcohol (PA) has cytotoxic effects on human cancer cell lines, including inhibiting cell growth, migration, and invasion. However, the exact molecular mechanism of PA in human castration-resistant prostate cancer (CRPC) cells remains unclear. Methods: DU145 and PC-3 cells were treated with different concentrations of PA for 48 h. Cell counting kit-8 (CCK-8), colony formation, and 5-ethynyl-2'-deoxyuridine (EdU) staining were used to detect cell proliferation. Scratc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…However, very few reports have examined the anti-cancer activity of PA and potential mechanisms of PCa. Our previous research demonstrated that PA inhibited the cell proliferation, migration, and invasion, and induced the apoptosis of PCa cells (18). In the present study, network pharmacology predicted that GPBAR1 was a PA target.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…However, very few reports have examined the anti-cancer activity of PA and potential mechanisms of PCa. Our previous research demonstrated that PA inhibited the cell proliferation, migration, and invasion, and induced the apoptosis of PCa cells (18). In the present study, network pharmacology predicted that GPBAR1 was a PA target.…”
Section: Discussionsupporting
confidence: 55%
“…In this study, we found GPBAR1 inhibited the phosphorylation of IkBα, which promoted p65 phosphorylation release in vivo and in vitro (29). We previously showed that PA induced PCa cell apoptosis by inhibiting NF-κB activity (18). Together, these findings indicate that PA inhibits PCa progression through the GPBAR1/NF-κB pathway.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…46 The genetics and histological characteristics of murine melanoma are known to be similar to those of human melanoma. 47 PA exhibited growth inhibitory activity not only against mouse melanoma B16F10 cells, but also against human prostate cancer cells (PC3 and DU145), lung cancer cells (A549) and colorectal cancer cells (HCT116 and SW480), [25][26][27] suggesting that it had the potential of anti-cancer in both mouse and human cancers. The findings indicate that PA may be a potential compound for the development of novel drugs or adjuvants that can be used in combination with clinical drugs to improve side effects and drug resistance.…”
Section: Discussionmentioning
confidence: 99%